Cellular ATP levels are affected by moderate and strong static magnetic fields. Issue 5 (30th April 2018) - Wang, Dongmei; Wang, Ze; Zhang, Lei; Li, Zhiyuan; Tian, XiaoFei; Fang, Jun; Lu, Qingyou; Zhang, Xin
Abstract : Mitochondrion is the major cellular energy producing organelle that is at the boundary between chemical reactions and physical processes. Although mitochondria have been shown to be affected by physical methods such as nonthermal plasma, whether static magnetic field (SMF) could also affect them is still unclear. Here we used rat adrenal PC12 cells to compare SMFs of different intensities for their effects on ATP (adenosine‐5′‐triphosphate), the major energy source produced by mitochondria, which is essential for various cellular processes. Our results show that although 0.26 or 0.50 T SMFs did not affect ATP, 1 T and 9 T SMFs affected ATP level differently and time‐dependently. Moreover, SMF‐induced ATP level fluctuations are correlated with mitochondrial membrane potential changes. Our study provides insights not only into understanding various cellular effects of SMFs, but also the potential clinical applications of SMFs. Bioelectromagnetics. 39:352–360, 2018. © 2018 Wiley Periodicals, Inc.